Kualitas Kehidupan Kerja, Keterlibatan Kerja Dan Kepuasan Kerja Karyawan PT. WOM Cabang Bengkulu - Sri Ekowati; Tika Ariani (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine the quality of work life and work involvement on job satisfaction of employees at PT. WOM Finance Bengkulu Branch. The sample used in this study were all 70 employees. This type of research uses quantitative research by distributing questionnaires for data collection. The results of the study indicate that the variables of quality of work life and work involvement have a positive and significant effect on job satisfaction.